Application of Hollow-Core Photonic Crystal Fibers in Gas Raman Lasers Operating at 1.7 μm - Jun Li; Hao Li; Zefeng Wang (Crystals, 2021)
A 1.7 μm pulsed laser plays an important role in bioimaging, gas detection, and so on. Fiber gas Raman lasers (FGRLs) based on hollow-core photonic crystal fibers (HC-PCFs) provide a novel and effective method for fiber lasers operating at 1.7 μm. Compared with traditional methods, FGRLs have more advantages in generating high-power 1.7 μm pulsed lasers. This paper reviews the studies of 1.7 μm FGRLs, briefly describes the principle and characteristics of HC-PCFs and gas-stimulated Raman scattering (SRS), and systematical characterizes 1.7 μm FGRLs in aspects of output spectral coverage, power-limiting factors, and a theoretical model. When the fiber length and pump power are constant, a relatively high gas pressure and appropriate pump peak power are the key to achieving high-power 1.7 μm Raman output. Furthermore, the development direction of 1.7 μm FGRLs is also explored.